Scribble influences cyst formation in autosomal‐dominant polycystic kidney disease by regulating Hippo signaling pathway. Issue 8 (12th March 2018) - Xu, Dechao; Lv, Jiayi; He, Liangliang; Fu, Lili; Hu, Ruikun; Cao, Ying; Mei, Changlin
Abstract : Polarity complexes, including the PAR (Partitioning‐defective), CRB (Crumbs) and SCRIB (Scribble) complexes, are required for the physiologic establishment, stabilization, and maintenance of a functional apical‐basolateral polarity. Inactivation of some of the polarity complexes results in cystic kidneys, and apical‐basolateral polarity defects are commonly observed in autosomal‐dominant polycystic kidney disease (ADPKD); however, little is known about the role that polarity complexes play in ADPKD. Here, we demonstrate that Scribble, a core protein of the SCRIB complex, is down‐regulated in ADPKD cell lines and the zebrafish model of this disease (pkd2 mor‐phants). Overexpression of Scribble could reduce cyst formation in pkd2 morphants, and loss of scrib led to a dilated pronephric duct in zebrafish. Furthermore, the Hippo signaling pathway was inactivated in scrib mutants and pkd2 morphants in which Yes‐associated protein (YAP), which is physiologically locatedinthe cytoplasm, was translocated to the nucleus. Of note, overexpression of cytoplasmic YAP, instead of nuclear YAP, could reduce cyst formation in pkd2 morphants. Consistently, knockout of yap resulted in cystic kidneys in zebrafish, which was rescued by the overexpression of cytoplasmic YAP, but not nuclear YAP. Finally, scrib and yap had a genetic interaction with pkd2 in cyst formation, and the overexpression of Scribble attenuated the down‐regulation of cytoplasmic YAP in ADPKD. Altogether, our data indicate that Scribble induces the phosphorylation of YAP and, consequently, influences cyst formation in ADPKD by mediating YAP nucleocytoplasmic shuttling.—Xu, D., Lv, J., He, L., Fu, L., Hu, R., Cao, Y., Mei, C. Scribble influences cyst formation in autosomal‐dominant polycystic kidney disease by regulating Hippo signaling pathway. FASEB J . 32, 4394–4407 (2018). www.fasebj.org